The informed and oriented transport system user - Peter Zimmermann (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2009)
The German Ministry of Transport, Building and Urban Affairs has set up a vision which shall improve the situation of the transport system user (in Germany). In order to make use of all resources an intensive co-ordination with the Ministry of Economics and Technology (transport research programme) was undertaken. Originally the project was called Meta-Data-Platform. In course of time the vision of a benefit for an oriented and informed transport system user developed. The Meta-Data-Platform shall enable data exchange of various sources, shall provide common interfaces and protocols, shall allow for exchange of geographical data of different formats and enable business processes between service and content provider organizations. Traffic data shall become more reliable, be of higher quality and access to real time data shall be possible. State authorities for controlling traffic, broadcasting stations for traffic warning news, service providers for individual route recommendations and content owners can make use of the system. The services of the meta data platform can be used as a virtual internet portal. Centralized services for judgment of data quality transfer of different interfaces and protocols and transfer of different geographical formats will be offered separately. Despite having intermodal transport in mind, there will be separate platforms for road and public transport. The realization has been splitted into a bunch of individual projects. Some of the projects have just been started. For some of them call for tenders are presently prepared. Development will take approximately four years. At the end of the development there will be test fields used for validation. Validation will be done with model services.
Keywords: 330